Postural responses to changing task conditions in patients with cerebellar lesions. Issue 5 (1st November 1998) - Mummel, P; Timmann, D; Krause, U W H; Boering, D; Thilmann, A F; Diener, H C; Horak, F B
Abstract : OBJECTIVE: To investigate the role of the cerebellum in postural adaptation for changes to the stimulus type of support surface displacements (backward translations v "toes up" rotations). METHODS: A group of 13 patients with chronic, isolated lesions of the cerebellum and 15 control subjects were tested. Automatic postural responses of the medial gastrocnemius and anterior tibial muscles were recorded. The first paradigm consisted of 10 rotational perturbations followed by 10 backward translations of the platform, and 10 backward translations followed by 10 rotations. The second paradigm consisted of 18 rotations and two randomly interposed translational perturbations, and 18 translations with two rotations randomly interposed. RESULTS: When the type of perturbation changed from an expected translation to an unexpected rotation and vice versa both control subjects and cerebellar patients showed an immediate and significant change in the response amplitude of the medial gastrocnemius and at the same time an immediate and significant change in the response amplitude of the anterior tibial muscles. Neither controls nor cerebellar patients showed effects of prediction in surface displacements of unexpected types of perturbation. Both controls and cerebellar patients showed no gradual increase in the gastrocnemius response in subsequent trials of surface translations following a block of 10 surface rotations and no gradual increase in the response amplitude of the anterior tibial muscle in subsequent trials of surface rotations following a block of 10 surface translations. CONCLUSIONS: Despite postural hypermetria, the integrity of the cerebellum does not seem critical for adaptation of postural synergies to changing stimulus types of surface displacements. The present results support previous findings suggesting that the main role of the cerebellum in automatic postural responses may be gain control.